1996
DOI: 10.1128/jb.178.20.6013-6018.1996
|View full text |Cite
|
Sign up to set email alerts
|

Role of NAD in regulating the adhE gene of Escherichia coli

Abstract: The fermentative alcohol dehydrogenase of Escherichia coli is encoded by the adhE gene, which is induced under anaerobic conditions but repressed in air. Previous work suggested that induction of adhE might depend on NADH levels. We therefore directly measured the NAD ؉ and NADH levels for cultures growing aerobically and anaerobically on a series of carbon sources whose metabolism generates different relative amounts of NADH. Expression of adhE was monitored both by assay of alcohol dehydrogenase activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(117 citation statements)
references
References 35 publications
7
109
1
Order By: Relevance
“…1). Previous reports indicate that E. coli with a ppc knockout does not grow on glucose as the sole carbon source (1,17,22,24,33). In our present study, ALS961 (YYC202 ppc) similarly did not grow aerobically in shake flasks with GAM medium.…”
Section: Production Of Lactatesupporting
confidence: 44%
See 1 more Smart Citation
“…1). Previous reports indicate that E. coli with a ppc knockout does not grow on glucose as the sole carbon source (1,17,22,24,33). In our present study, ALS961 (YYC202 ppc) similarly did not grow aerobically in shake flasks with GAM medium.…”
Section: Production Of Lactatesupporting
confidence: 44%
“…Thus, the presence of these two pathways for acetate assimilation does not significantly affect the overall redox balance and may merely offer the cells a means to fine tune the redox environment as the culture enters and during anaerobic conditions. Second, previous research with wild-type E. coli indicates that the NADH/NAD ratio under aerobic conditions is less than half of the value under anaerobic conditions (17). The sudden change from aerobic growth to anaerobic conditions could therefore result in a temporary deficit in NADH until a new, higher steady-state NADH/NAD ratio is attained.…”
Section: Vol 73 2007mentioning
confidence: 99%
“…ebi.ac.uk/Tools/pfa/iprscan/) suggests that both the alcohol and the aldehyde dehydrogenase domains are present in ADH2, whereas ADH3 possesses only the alcohol dehydrogenase domain. In the Enterobacteriaceae, the AdhE enzyme represents the major route for recycling NADH during fermentation (Clark and Cronan, 1980;Leonardo et al, 1996), as highlighted by the inability of an E. coli adhE mutant to grow on minimal medium under anoxic conditions (Cunningham and Clark, 1986;Gupta and Clark, 1989). Interestingly, an AdhE/ADH1 homolog is not present in the majority of prokaryotes, and among the eukaryotes, it has only been identified in a few amitochondriate protists and some green algae (Atteia et al, 2003(Atteia et al, , 2006.…”
mentioning
confidence: 99%
“…The lower NADH/NAD + ratio correlates with the reduced production of the less energyefficient fermentative gene adhE and the repression of the alcohol dehydrogenase activity. Indeed, Leonardo et al (1996), by directly measuring the NADH-NAD + levels and by monitoring the expression of adhE, demonstrated that this E. coli gene is induced under high-NADH/NAD + conditions and repressed under low-NADH/NAD + conditions. The decrease of NADH/NAD + also prevents the inactivation of another enzyme subject to catabolite repression, the AceE enzyme in the pyruvate dehydrogenase complex (required for the oxidative carboxylation of pyruvate to produce CO 2 and acetyl-CoA).…”
Section: Discussionmentioning
confidence: 99%